Ultrasound-Guided Regional Anesthesia for Procedures of the Upper Extremity - Farheen Mirza; Anthony R. Brown (Anesthesiology Research and Practice)
Anesthesia options for upper extremity surgery include general and regional anesthesia. Brachial plexus blockade has several advantages including decreased hemodynamic instability, avoidance of airway instrumentation, and intra-, as well as post-operative analgesia. Prior to the availability of ultrasound the risks of complications and failure of regional anesthesia made general anesthesia a more desirable option for anesthesiologists inexperienced in the practice of regional anesthesia. Ultrasonography has revolutionized the practice of regional anesthesia. By visualizing needle entry throughout the procedure, the relationship between the anatomical structures and the needle can reduce the incidence of complications. In addition, direct visualization of the spread of local anesthesia around the nerves provides instant feedback regarding the likely success of the block. This review article outlines how ultrasound has improved the safety and success of brachial plexus blocks. The advantages that ultrasound guidance provides are only as good as the experience of the anesthesiologist performing the block. For example, in experienced hands, with real time needle visualization, a supraclavicular brachial plexus block has changed from an approach with the highest risk of pneumothorax to a block with minimal risks making it the ideal choice for most upper extremity surgeries.